2000
DOI: 10.1016/s1097-2765(00)80264-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA Ligase IV Deficiency in Mice Leads to Defective Neurogenesis and Embryonic Lethality via the p53 Pathway

Abstract: DNA ligase IV (LIG4) is a nonhomologous end-joining (NHEJ) protein used for V(D)J recombination and DNA repair. In mice, Lig4 deficiency causes embryonic lethality, massive neuronal apoptosis, arrested lymphogenesis, and various cellular defects. Herein, we assess potential roles in this phenotype for INK4a/ARF and p53, two proteins implicated in apoptosis and senescence. INK4a/ARF deficiency rescued proliferation/senescence defects of Lig4-deficient fibroblasts but not other phenotypic aspects. In contrast, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
350
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(379 citation statements)
references
References 57 publications
27
350
1
1
Order By: Relevance
“…However, a limitation is that mouse studies do not allow a precise dissection and separation of distinct endpoints such as chromosomal instability and survival. The majority of multiple pathway analysis using mice has focused on genetic crosses involving p53 (see for example [30][31][32][33][34]). Since p53 has critical roles in apoptosis and cell cycle checkpoint arrest, the interplay between defined pathways cannot be established.…”
Section: Other Studies Examining the Interplay Between Damage Responsmentioning
confidence: 99%
“…However, a limitation is that mouse studies do not allow a precise dissection and separation of distinct endpoints such as chromosomal instability and survival. The majority of multiple pathway analysis using mice has focused on genetic crosses involving p53 (see for example [30][31][32][33][34]). Since p53 has critical roles in apoptosis and cell cycle checkpoint arrest, the interplay between defined pathways cannot be established.…”
Section: Other Studies Examining the Interplay Between Damage Responsmentioning
confidence: 99%
“…Signals that induce DNA damage response, such as ionizing irradiation (IR) and chemotherapeutic drugs, or telomere dysfunction, drive senescence through the p53-p21 pathway (Zuckerman et al, 2009). Impairment of DNA repair genes, such as BRCAI or DNA ligase IV, allows DNA to accumulate damage, which induces premature senescence in MEFs; this can be evaded by p53 inactivation (Frank et al, 2000). Irreparable DNA lesions sustain the ATM/ATR-p53 response, maintaining the senescence phenotype (Campisi and d'Adda di Fagagna, 2007;Di Micco et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is also sensitively activated in the IZ compartment, although less readily than in the VZ/SVZ [96]. Importantly, DNA ligase IV null embryos die between E13.5 and E16.5 from massive neuronal apoptosis, suggesting that endogenous DSBs may arise from the rapid cell division at this developmental stage [40,97]. Loss of p53 relieved both the neuronal apoptosis and embryonic cell death conferred by loss of DNA ligase IV [97].…”
Section: How Does Nhej Deficiency Confer Microcephaly and Growth Delaymentioning
confidence: 99%
“…Importantly, DNA ligase IV null embryos die between E13.5 and E16.5 from massive neuronal apoptosis, suggesting that endogenous DSBs may arise from the rapid cell division at this developmental stage [40,97]. Loss of p53 relieved both the neuronal apoptosis and embryonic cell death conferred by loss of DNA ligase IV [97]. Studies on neurogenesis using a mouse model for LigIV Syndrome (LigIV Y288C ) showed small heads (as well as small bodies) and elevated apoptosis in the VZ/SVZ and IZ compartments [95].…”
Section: How Does Nhej Deficiency Confer Microcephaly and Growth Delaymentioning
confidence: 99%